EFEKTIVITAS ALAT PENYARING POLUTAN DENGAN ADSORBANSI ARANG AKTIF DAUN TREMBESI (SAMANEA SAMAN) - Mulyadi Abdul Wahid; Al-Hafidh Rahman; Hadi Kurniawan (Program Studi Teknik Lingkungan Fakultas Sains dan Teknologi UIN Ar-Raniry Banda Aceh, 2021)
The air existence on the surface of the earth is one of the important factors for the survival of living things on it. Indonesia’s quality of ambient air has decreased and it is categorized as not good for sensitive groups. The biggest cause of air pollution comes from motor vehicles, of which 85% is from combustion in motorized vehicle engines. Trembesi is the most effective plant in adsorbing pollutant carbon in the air. Activated charcoal is the carbon that has better absorption of cations, anions and the molecules of organic and inorganic compounds. This study aims to create a pollutant filter equipment for CO and CO2 made from Trembesi leaves activated charcoal. This research was conducted by creating an air pollutant filter with 3 different types of adsorbent, namely adsorbent made from paper pulp, trembesi leaves extract adsorbent, and trembesi leaves activated charcoal adsorbent. The data collection used 2 types of vehicles with different year of release and engines. The measurement of pollutant concentration using a Gas Analyzer instrument tester with Korean Iyasaka AET-4000Q type. The result of this study showed that the best adsorbent is activated charcoal from trembesi leaves with 100% adsorption of CO and 36,29% adsorption of CO2 using 2018 Toyota Agya car Dual VVT-I engines with eco indicator technology, and for 1988 SE 1,3 Starlet car with a carburetor type engine successfully adsorb CO by 9,65% and 7,2% for CO2.